2022
DOI: 10.2147/jir.s359908
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immune-Related Key Genes as Potential Diagnostic Biomarkers of Sepsis in Children

Abstract: Objective The pathogenesis of sepsis is still unclear due to its complexity, especially in children. This study aimed to analyse the immune microenvironment and regulatory networks related to sepsis in children at the molecular level and to identify key immune-related genes to provide a new basis for the early diagnosis of sepsis. Methods The GSE145227 and GSE26440 datasets were downloaded from the Gene Expression Omnibus. The analyses included differentially expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Compared to previous studies, our work introduces a novel approach for the early diagnosis of sepsis by employing an REO-based algorithm. Lu et al [ 14 ] utilized modified Lasso penalized regression and Random Forest to construct an IRG classifier, and Wang et al [ 54 ] focused on pediatric sepsis using various bioinformatics analyses; our study is the first to identify three immune-related gene pairs using an REO-based algorithm. Additionally, unlike Peng et al [ 20 ], whose focus was on predicting 28-day mortality in patients with sepsis, our study aimed at early diagnosis in a broader population with a substantially larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to previous studies, our work introduces a novel approach for the early diagnosis of sepsis by employing an REO-based algorithm. Lu et al [ 14 ] utilized modified Lasso penalized regression and Random Forest to construct an IRG classifier, and Wang et al [ 54 ] focused on pediatric sepsis using various bioinformatics analyses; our study is the first to identify three immune-related gene pairs using an REO-based algorithm. Additionally, unlike Peng et al [ 20 ], whose focus was on predicting 28-day mortality in patients with sepsis, our study aimed at early diagnosis in a broader population with a substantially larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis is characterized by upregulation of CD4 + and CD8 + T cells, T helper 17 cells, and regulatory T cells [ 16 ], lymphopenia, and loss of immune function. Microarray analysis has indicated abnormalities in the expression of immune-related genes in children with sepsis, including FYN, FBL, ATM, WDR75, FOXO1, and ITK [ 18 ]. Alterations in gene expression related to innate immunity have also been reported in NS [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…While most commonly accepted measures were highly variable and did not change significantly, there were changes in CD8 + T cells and a clear significant downward trend in deceased children. The level of CD8 + lymphocytes is a rare and variable finding among sepsis biomarkers; however, CD8 + T cells were previously described to play a key role in mice [ 23 ] and as a biomarker of early neonatal sepsis [ 24 , 25 , 26 ]. In particular, Carey et al [ 27 ] reported that the number of unique T cell receptors is limited during the first trimester.…”
Section: Discussionmentioning
confidence: 99%